Effect of substituting spray-dried plasma protein for milk products in starter pig diets - J A Hansen; K G Friesen; T L Weeden; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1990)
Two growth trials utilizing 444 weaned pigs were conducted to determine the efficacy of substituting spray-dried porcine plasma protein (PP) for dried skim milk (DSM) and/or dried whey (DW) in starter pig diets. Trial 1 was a field study in which 240 pigs were fed either a control diet containing 20% DSM and 20% DW during phase I (0 to 14 d postweaning) and 15% DW and 5% select menhaden fishmeal in phase II (14 to 28 d postweaning) of the 28 d trial. Plasma protein was substituted on a lysine basis for DSM in the phase I diet and for DW in the phase IT diet. Diets were isolactose in both phases. Pigs fed the diets containing PP grew faster and consumed more feed from d 0 to 7 than pigs fed the control. However, pigs fed the control diet compensated during wk 2 to achieve equal performance during phase 1. No treatment differences were detected during phase II or in overall performance. In Trial 2, 204 pigs were allotted to one of the following treatments: 1) control diet containing 20% DSM and 20& DW, 2) as 1 with casein replacing soybean meal (lysine basis; all milk protein), 3) as 1 with PP and lactose replacing 20% DSM (lysine and lactose basis), 4) as 3 with starch replacing lactose (wt/wt), 5) as 1 with PP and lactose replacing DSM and DW (lysine and lactose basis), 6) as 5 with starch replacing lactose, 7) corn-soybean meal plus 20% DW Pigs fed diets containing PP grew faster and consumed more feed than pigs fed the control, casein, or 20% DW diets from 0 to 14 d postweaning. Similarly, overall gains were significantly greater for pigs fed PP than pigs fed the control, casein, and DW diets. Also, pigs fed PP consumed greater quantities of feed over the entire trial than those pigs fed the control or casein diets. Serum was collected on d 13 and analyzed for blood urea nitrogen. Blood urea N was higher for pigs fed PP, indicating that the amino acids in PP are more available to the pig, but not all are utilized for protein synthesis. Skinfold thickness was measured on d 7 following intradermal injections of protein extracts of PP soybean meal and DSM; these data indicate that PP and DSM cause extremely small changes in skinfold thickness compared to soybean proteins. Based on the results of these experiments, PP has an equal, if not better, feeding value than milk protein.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Starter performance; DSM; Whey; Plasma protein